Electroactive layer-by-layer films of iron tetrasulfonated phthalocyanine - Zucolotto, V; Ferreira, M.; Cordeiro, M. R.; Constantino, CJL; Moreira, W. C.; Oliveira, O. N. (Elsevier B.V., 2003)
Electroactive films of iron tetrasulfonated phthalocyanine (FeTsPc) were assembled via the electrostatic layer-by-layer technique (LBL), in which FeTsPc layers were alternated with the polycationic poly(allylamine hydrochloride) (PAN). The multilayer formation was monitored via UV-Vis spectroscopy by measuring the increase in the Q Band of FeTsPc at 676 nm. Film thickness was estimated by profilometry as ca. 10 Angstrom per bilayer. Fourier transform infrared and UV-Vis absorption spectroscopy suggested specific interactions between FeTsPc and PAR Cyclic voltammograms showed reproducible pairs of oxidation-reduction peaks at 0.92 mV and 0.70 mV, respectively, for a 50-bilayer PAH/FeTsPc film at 50 mV/s (vs Ag/AgNO3).
Keywords: layer by layer; phthalocyanines; electrochemical methods; organic/inorganic interfaces